Polymer particles with structural color rendering
By adjusting the acid value for polymer particles, the problem of a lot of debris and attachments during polymerization is solved, high yield and high productivity are achieved, and structural color development is achieved, which is suitable as a material for presenting structural color.
Patent Information
- Application Number
- CN202180021135.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-03-25
- Filing Date
- 2021-03-24
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2041-03-24
AI Technical Summary
In the prior art, debris during polymerization and attachments on the inner wall of the polymerization device are produced more, resulting in low yields of polystyrene-based polymers and low concentrations of solid components, resulting in poor productivity.
By making the polymer particles have a specific acid value (5 to 38 mgKOH/g) in a specific range, even at a high solid content concentration, the generation of debris and adhesions during polymerization can be reduced, and the polymerization yield can be improved.
High yield and low debris production during polymerization at high solid content concentrations are achieved, the productivity of polymer particles is improved, and excellent structural color development is achieved.
Smart Images

Figure BDA0003845030740000151
Abstract
Description
Technical Field
[0001] The present invention relates to polymer particles having structural color development, an emulsion and a structure composed of the polymer particles, and an article having the structure. Background Art
[0002] In recent years, the toxicity of azo pigments containing heavy metals has been a concern. In addition, there is a problem of poor light resistance in dyes. Therefore, in order to provide a coloring material with low toxicity and good light resistance, a material that exhibits structural color is configured on the surface of a molded body. By configuring a material that exhibits structural color on the surface of a molded body, it is expected that special effects such as a coloring material with good light resistance can be provided without using heavy metals.
[0003] Various materials have been studied as substances that exhibit structural colors. However, polymer fine particles are often used as the material because they are easy to produce. Among them, polystyrene polymers are preferably used as the material.
[0004] As a method for producing a polystyrene-based polymer used as a material for a substance exhibiting structural color, a method of producing the polystyrene-based polymer by soap-free emulsion polymerization has been proposed (see Non-Patent Document 1).
[0005] In addition, as a method for obtaining a structural color coating film-forming coating composition, a method of producing core-shell type polymer fine particles by soap-free emulsion polymerization has been proposed (see Patent Document 1).
[0006] In addition, a method of obtaining acrylic polymer fine particles as polymer powder by soap-free emulsion polymerization has been proposed (see Patent Document 2).
[0007] Prior art literature
[0008] Non-patent literature
[0009] Non-patent document 1: Journal of Applied Polymer Science, Vol. 107, p. 3903-3908 (2008)
[0010] Patent Literature
[0011] Patent Document 1: Japanese Patent Application Publication No. 2009-249527
[0012] Patent Document 2: International Publication No. 2013 / 062123 Summary of the invention
[0013] The production method proposed in Non-Patent Document 1 has the problem that a large amount of debris and deposits on the inner wall of the polymerization device are generated during polymerization, and the yield of the polystyrene polymer is low. In addition, there is a problem that the productivity is poor due to the low solid content concentration (10% by mass) during polymerization.
[0014] The method proposed in Patent Document 1 has a problem of poor productivity due to the low solid content concentration (20% by mass) during polymerization. In addition, since the monomers used in the core layer polymerization are styrene, methyl methacrylate, and divinylbenzene, and the core layer is a polymer without an acid value, there is a problem of a large amount of debris and attachments to the inner wall of the polymerization device during polymerization, and a low polymer yield.
[0015] In the method proposed in Patent Document 2, the volume average primary particle size of the obtained acrylic polymer particles is 600 nm or more, and the structure obtained when the polymer particles are arranged does not have structural color rendering in the visible light region. In addition, the purpose of Patent Document 2 is to spray-dry the polymer particles obtained in an emulsion state to form a powder, and there is no suggestion about structural color rendering.
[0016] The present disclosure aims to solve the above-mentioned problems and to provide polymer particles used as a material for a substance exhibiting structural color, which produce less debris during polymerization and less deposits on the inner wall of a polymerization device even at a high solid content concentration.
[0017] The present inventors have repeatedly conducted intensive studies to solve the above-mentioned problems and have found that by making the polymer fine particles have an acid value within a specific range, the generation of debris during polymerization and adhesion to the inner wall of the polymerization device can be reduced even at a high solid content concentration, thereby completing the present disclosure.
[0018] That is, the gist of the present disclosure is as follows.
[0019] [1] A polymer fine particle having a number average particle size of 50 to 450 nm, a CV value of the particle size based on the number of particles of 5% or less,
[0020] The acid value is 5-38 mgKOH / g.
[0021] [2] The polymer fine particles according to [1], wherein the polymer fine particles are preferably particles having a uniform resin composition.
[0022] [3] The polymer fine particles according to [1] or [2], wherein the Tg of the polymer fine particles is preferably 50° C. or higher.
[0023] [4] The polymer fine particles according to any one of [1] to [3], wherein the polymer fine particles are preferably composed of a polystyrene polymer.
[0024] [5] The polymer fine particles according to [4], wherein the polystyrene polymer preferably contains acrylic acid units and / or methacrylic acid units.
[0025] [6] An emulsion, wherein the polymer fine particles according to any one of [1] to [5] are dispersed in a medium mainly composed of water.
[0026] [7] A structure in which the polymer fine particles according to any one of [1] to [5] are arranged and develop color.
[0027] [8] An article comprising the structure of [7] formed on a substrate.
[0028] [9] The article according to [8], wherein the article is preferably in a film-like shape.
[0029]
[10] A polymer particle having structural color rendering properties when arranged.
[0030] The acid value is 5-38 mgKOH / g.
[0031]
[11] The polymer fine particles according to
[10] , wherein the polymer fine particles are preferably particles having a uniform resin composition.
[0032]
[12] The polymer fine particles according to
[10] or
[11] , wherein the Tg of the polymer fine particles is preferably 50°C or higher.
[0033]
[13] The polymer fine particles according to any one of
[10] to
[12] , wherein the polymer fine particles are preferably composed of a polystyrene polymer.
[0034]
[14] The polymer fine particles according to
[13] , wherein the polystyrene polymer preferably contains acrylic acid units and / or methacrylic acid units.
[0035]
[15] An emulsion, wherein the polymer fine particles according to any one of
[10] to
[14] are dispersed in a medium mainly composed of water.
[0036]
[16] A structure in which the polymer fine particles according to any one of
[10] to
[14] are arranged and develop color.
[0037]
[17] An article, wherein the structure of
[16] is formed on a substrate.
[0038]
[18] The article according to
[17] is preferably in the shape of a film.
[0039] The polymer microparticles disclosed herein have little debris during polymerization and adhesion to the inner wall of the polymerization device, even at a high solid content concentration, and can therefore be produced at a high yield. In addition, since they have excellent structural color development properties, they are suitable as a material for a substance that exhibits structural color.
[0040] The material exhibiting structural color of the present disclosure exhibits excellent structural color development and is therefore suitable for improving the design properties of an article. DETAILED DESCRIPTION
[0041] Hereinafter, an embodiment of the present invention will be described in detail. However, the description of the components described below is an example (representative example) of the embodiment of the present invention, and the present invention is not limited to the following contents unless exceeding the gist thereof.
[0042] In addition, when the expression "to" is used in this specification, it is used to include the numerical values or physical values described before and after it. In addition, the numerical values or physical values described as the upper limit or the lower limit are used to include the value.
[0043] The polymer fine particles have a number average particle size of 50 to 450 nm, a number-based CV value of the particle size of 5% or less, and an acid value of 5 to 38 mgKOH / g.
[0044] [Number average particle size]
[0045] The number average particle size of the polymer microparticles is 50 to 450 nm.
[0046] When the number average particle size is within the above range, the structural color rendering property is good.
[0047] The method for determining the number average particle size is described in the Examples.
[0048] The number average particle size of the polymer fine particles can be adjusted to the above range by adjusting the types and blending ratios of monomer components other than styrene and the acidic monomer during production, for example.
[0049] [CV value of particle size based on number]
[0050] The CV value of the particle size of the polymer fine particles based on number is 5% or less.
[0051] The CV value is also called “coefficient of variation” or “relative standard deviation”, and is calculated by (standard deviation / average particle size)×100 in the present disclosure.
[0052] When the CV value of the particle size based on the number is within the above range, the structural color development property is good.
[0053] The method for measuring the CV value of the particle size based on the number is as described in the Examples.
[0054] The CV value of the particle size based on the number of polymer microparticles can be adjusted by, for example, selecting a polymerization method or sieving the pulverized product after polymerization during production as described later, and may be 5% or less.
[0055] [Acid value]
[0056] The acid value of the polymer microparticles is 5 to 38 mgKOH / g.
[0057] When the acid value is 5 mgKOH / g or more, debris during polymerization is reduced, and when it is 38 mgKOH / g or less, stability during polymerization is improved.
[0058] The acid value of the polymer fine particles can be adjusted to the above range by, for example, adjusting the blending ratio of the acidic monomer constituting the polymer fine particles when producing the polymer fine particles.
[0059] [Particles with uniform resin composition]
[0060] The polymer fine particles are preferably particles having a uniform resin composition.
[0061] Particles with uniform resin composition mean that when the polymer particles are copolymers, the resin composition is substantially the same throughout the polymer particles. In other words, it means that the resin composition is substantially uniform throughout the particles, for example, it means that there is no variation in the resin composition except for the variation in the composition that is inevitable in production.
[0062] Particles having a uniform resin composition are produced, for example, by maintaining the same composition of monomers supplied without changing the composition from the initial stage of polymerization to the final stage of polymerization.
[0063] Particles having a uniform resin composition are preferred because the difference in refractive index between the inside and outside of the particles becomes larger and the structural color rendering property improves.
[0064] [Tg is 50°C or higher]
[0065] The polymer fine particles preferably have a Tg of 50° C. or higher. In order to make the Tg of the polymer fine particles 50° C. or higher, a polymer having a Tg of 50° C. or higher may be used and formed into fine particles.
[0066] Examples of polymers having a Tg of 50° C. or higher include polyamides, polyimides, low-density polyethylene, high-density polyethylene, poly(meth)acrylates, polystyrene polymers such as polystyrene and its derivatives, polyvinyl chloride, phenolic resins, and polycarbonates.
[0067] Among them, poly(meth)acrylates and polystyrene polymers are preferred because raw materials are easily available and fine particles having a uniform particle size can be easily produced. Polystyrene polymers are more preferred because a polymer having a high refractive index can be obtained.
[0068] A polymer having a high refractive index is preferred because it increases the difference in refractive index between the inside and outside of the particle and improves structural color development.
[0069] In addition, in this specification, (meth)acrylic acid means acrylic acid and / or methacrylic acid.
[0070] The Tg of the polymer fine particles is more preferably 60°C or higher, and further preferably 70°C or higher.
[0071] When the Tg of the polymer fine particles is 50° C. or higher, the structure is maintained even in a high-temperature usage environment, and therefore, the Tg is preferably 50° C. or higher.
[0072] As described above, the polymer fine particles preferably have a Tg of 50° C. or higher. In this case, the polymer fine particles may be composed of a non-crosslinked polymer or a crosslinked polymer.
[0073] In addition, Tg is a value calculated according to Fox's formula.
[0074] [Poly (meth)acrylates]
[0075] Poly(meth)acrylates refer to polymers containing (meth)acrylate units as main components. Here, the main component means that the content of the (meth)acrylate units is 50% by mass or more, and further 60% by mass or more, relative to the entire polymer.
[0076] Examples of the (meth)acrylic acid esters that are raw materials for the (meth)acrylic acid ester units include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, and butyl (meth)acrylate.
[0077] Among them, methyl (meth)acrylate is preferred, and methyl methacrylate is more preferred, since the Tg of the obtained polymer is 50° C. or higher.
[0078] The poly(meth)acrylates may be random copolymers or block copolymers, but are usually random copolymers.
[0079] In addition to the above-mentioned (meth)acrylates, poly(meth)acrylates may be copolymerized with any monomers.
[0080] [Polystyrene polymers]
[0081] The polystyrene polymer refers to a polymer having styrene units as a main component. Here, the main component means that the content of the styrene units is 50% by mass or more, and further 60% by mass or more, relative to the entire polymer.
[0082] The polystyrene-based polymer may be a random copolymer or a block copolymer, but is usually a random copolymer.
[0083] In order to achieve the effects of the present disclosure, the polystyrene polymer is in the form of fine particles having a uniform particle size (specifically, fine particles having a number average particle size of 50 to 450 nm and a CV value of 5% or less).
[0084] In order to obtain microparticles with uniform particle size, for example, there are methods such as obtaining a polymer of appropriate size by bulk polymerization, suspension polymerization, emulsion polymerization, solution polymerization, etc., crushing it into fine powder, and making the particle size uniform by sieving, etc. In addition, there is a method of directly obtaining microparticles with uniform particle size by soap-free emulsion polymerization.
[0085] Among them, the method using soap-free emulsion polymerization is preferred because of its excellent productivity.
[0086] [Monomer unit of polystyrene polymer]
[0087] The polystyrene polymer preferably contains a styrene unit and an acidic monomer unit. In other words, the polystyrene polymer is a copolymer of styrene and an acidic monomer, and preferably consists of a constituent unit derived from styrene and a constituent unit derived from an acidic monomer.
[0088] There are no particular limitations on styrene used as a raw material of the styrene unit, and general-purpose styrene may be used.
[0089] Examples of the acidic monomers that are raw materials for the acidic monomer units include monomers having a carboxyl group such as acrylic acid, methacrylic acid, maleic acid, fumaric acid, and cinnamic acid; monomers having a sulfonic acid group such as sulfonated styrene; and monomers having a sulfonamide group such as vinylbenzenesulfonamide.
[0090] Among them, acrylic acid and methacrylic acid are preferred, and acrylic acid is more preferred, since they are water-soluble and have a large effect of reducing debris during polymerization.
[0091] The acidic monomer may be used alone or in combination of two or more.
[0092] That is, the styrene polymer preferably contains an acrylic acid unit and / or a methacrylic acid unit in addition to the styrene unit as the main component, and more preferably contains an acrylic acid unit. In this case, the Tg of the polymer fine particles can be easily adjusted.
[0093] When introducing a cross-linked structure into a polystyrene polymer, a known multifunctional monomer may be copolymerized.
[0094] Examples of the polyfunctional monomer include divinylbenzene, hexanediol di(meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, hexaethylene glycol di(meth)acrylate, nonaethylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, and diallyl phthalate.
[0095] Among them, divinylbenzene and hexanediol diacrylate are preferred.
[0096] The polyfunctional monomer may be used alone or in combination of two or more.
[0097] In addition, in this specification, (meth)acrylate means acrylate and / or methacrylate.
[0098] The polystyrene polymer may further contain other monomer units. Other monomer units refer to monomer units other than the styrene unit, acrylic acid unit, and methacrylic acid unit.
[0099] Examples of other monomers that are raw materials for other monomer units include styrenes other than styrene, such as methylstyrene, chlorostyrene, dichlorostyrene, p-tert-butylstyrene, p-n-butylstyrene, and p-n-nonylstyrene; metal salts such as sodium salt of styrenesulfonic acid; (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, hydroxyethyl (meth)acrylate, and ethylhexyl (meth)acrylate; and acrylamides such as acrylamide, N-propylacrylamide, N,N-dimethylacrylamide, N,N-dipropylacrylamide, and N,N-dibutylacrylamide.
[0100] Among them, metal salts such as sodium salt of styrenesulfonic acid are preferred because the particle size can be well controlled.
[0101] [Composition of polystyrene polymer]
[0102] The polystyrene polymer preferably contains 80.0 to 99.75% by mass of styrene units. If the content of the styrene units is within the above range, the refractive index of the particles becomes high and the structural color development property is improved, which is preferred.
[0103] The content of the styrene unit is more preferably 90.0% by mass or more and more preferably 99.4% by mass or less.
[0104] The polystyrene polymer preferably contains 0.25 to 20.0% by mass of an acidic monomer unit. If the content of the acidic monomer unit is within the above range, debris during polymerization is reduced, which is preferred.
[0105] The content of the acidic monomer unit is more preferably 0.6% by mass or more and more preferably 10.0% by mass or less.
[0106] When the polystyrene polymer contains a multifunctional monomer unit and / or other monomer units, the content thereof is preferably 3% by mass or less. If the content of the multifunctional monomer unit and / or other monomer units is 3% by mass or less, the particle size can be well controlled, which is preferred.
[0107] The content of the polyfunctional monomer unit and / or other monomer units is more preferably 2% by mass or less.
[0108] [Method for producing polymer microparticles]
[0109] The polymer fine particles are preferably obtained by soap-free emulsion polymerization. Soap-free emulsion polymerization is a well-known polymerization method, and for example, it is described below.
[0110] Add ion exchange water to the reaction container, and add a polymerization aid while heating and stirring as needed to fully disperse the polymerization aid in the ion exchange water. Then, add a polymerization initiator while continuing to stir. Then, add monomers dropwise in sequence while continuing to stir to initiate a polymerization reaction. Particles are formed as the polymerization proceeds.
[0111] The composition of the monomers added dropwise sequentially is preferably the same from the initial stage to the final stage of the dropping.
[0112] The solid content concentration during polymerization, that is, the concentration of the polymer fine particles relative to the entire system during polymerization, is preferably 20 to 40% by mass.
[0113] If the solid content concentration during polymerization is not less than the above lower limit, the productivity of polymer microparticles will be improved. On the other hand, if it is not more than the above upper limit, there will be no generation of debris during polymerization and no attachment to the inner wall of the polymerization device.
[0114] When a polymerization initiator is used, the polymerization temperature is usually set to 60 to 90° C. After the reaction is completed, the polymer particles are taken out as an emulsion. The high solid content concentration in this specification means that the concentration of the solid content (specifically the polymer particles) during polymerization is, for example, 20% by mass or more.
[0115] Examples of the polymerization initiator used in the soap-free emulsion polymerization include water-soluble polymerization initiators such as sodium persulfate, potassium persulfate, and ammonium persulfate; oil-soluble polymerization initiators such as benzoyl peroxide and lauroyl peroxide; and redox polymerization initiators formed by a combination of an oxidizing agent and a reducing agent.
[0116] These may be used alone or in combination of two or more.
[0117] Among them, a water-soluble polymerization initiator is preferred from the viewpoint of easy handling.
[0118] In the present disclosure, for example, as monomers supplied to the polymerization system, in addition to the monomers that become the main component, acidic monomers such as acrylic acid and methacrylic acid are used from the early stage of polymerization, thereby further reducing the generation of debris during polymerization and adhesion to the inner wall of the polymerization device.
[0119] This can further improve the yield during polymerization and further improve the productivity of polymer fine particles.
[0120] In addition, in the prior art, in order to avoid the generation of debris during polymerization and attachments on the inner wall of the polymerization device, the solid content concentration is reduced to perform polymerization, but in the present disclosure, since the generation of debris and attachments can be reduced, the solid content concentration during polymerization can be increased. As a result, the productivity of polymer particles can be further improved.
[0121] [Lotion]
[0122] Since the polymer fine particles are obtained by soap-free emulsion polymerization, they are obtained in the state of emulsion. Here, emulsion means that the polymer fine particles are dispersed in a medium mainly composed of water.
[0123] The medium mainly composed of water means that the ratio of water is 50 mass % or more, and furthermore, 60 mass % or more.
[0124] As the component other than water, any organic solvent soluble in water can be selected.
[0125] The emulsion may be in a state obtained by soap-free emulsion polymerization, in a state in which an emulsion obtained by soap-free emulsion polymerization is appropriately diluted, or in a state in which polymer fine particles obtained in the form of powder are dispersed in a medium.
[0126] [Structural color rendering]
[0127] Polymer particles have structural color rendering, which means that particles with the same particle size will show structural color when they are arranged regularly.
[0128] Structural color development refers to the phenomenon that due to the regularly arranged crystal structure of particles, color is developed due to optical physical phenomena such as interference and scattering according to the wavelength of light.
[0129] Since the structural color rendering depends on the properties of light, it is manifested not only in the visible light region but also in the ultraviolet region and infrared region.
[0130] In order to express structural color development in the ultraviolet region, polymer fine particles with a small number average particle size may be used, and in order to express structural color development in the infrared region, polymer fine particles with a large number average particle size may be used.
[0131] In the present disclosure, structural color rendering is used to improve the design of the article, and therefore it is preferred to have structural color rendering in the visible light region.
[0132] Here, the visible light region refers to a wavelength of 360 to 830 nm, the ultraviolet region refers to a wavelength of 200 to 359 nm, and the infrared region refers to a wavelength of 831 to 2500 nm.
[0133] [Structure and method for manufacturing the same]
[0134] The structured body is a substance in which the polymer particles are periodically arranged to exhibit structural color, that is, in a color-developing state.
[0135] Here, the term "alignment" refers to the formation of colloidal crystals or colloidal amorphous aggregates of polymer particles.
[0136] A substance showing structural color is a substance that shows a color that is dependent on the observation angle because the arrangement of the particles causes diffraction and interference of light when polymer particles of uniform particle size are regularly arranged. The color changes depending on the observation angle.
[0137] The method for producing the structure is, for example, as follows.
[0138] An emulsion of polymer fine particles obtained by soap-free emulsion polymerization is appropriately diluted, and a dispersion of carbon black is added thereto. This is referred to as a "mixed sample."
[0139] After the carbon black is fully dispersed, the mixed sample is applied on a smooth substrate and then dried at an appropriate temperature to obtain the target product.
[0140] Since the particle size of polymer particles is uniform, they are periodically arranged and colloidally crystallized to present structural colors.
[0141] [Article and method of manufacturing the same]
[0142] The article is an article in which the above-mentioned structure is formed on a substrate.
[0143] The substrate is not particularly limited, and general materials such as metal, resin, wood, and paper can be used.
[0144] By coating the mixed sample on a substrate, an article showing structural color can be obtained. For the purpose of surface protection, a surface protection layer can be provided on the surface of the article showing structural color as needed.
[0145] [membrane]
[0146] The film is a substance in which the above-mentioned article is in the shape of a film.
[0147] In order to make the above-mentioned article into a film shape, a film-like material may be used as a substrate. For the purpose of surface protection, a surface protection layer may be provided on the surface of the film as required.
[0148] Example
[0149] The present invention will be described in further detail below with reference to Examples, but the present invention is not limited to the following Examples unless the gist of the present invention is exceeded.
[0150] In addition, in the following description, "part" and "%" respectively represent "part by mass" and "mass %".
[0151] In the following Examples and Comparative Examples, various physical properties were measured by the following methods.
[0152] [Evaluation method]
[0153] (1) Number average particle size
[0154] The polymer microparticle emulsion is applied to a substrate and dried, and then an image of the polymer microparticles is observed using an electron microscope at a magnification of 20,000 or more. The diameters of at least 400 particles in the image are measured, and the arithmetic average is calculated to obtain the number average particle diameter.
[0155] (2) CV value of particle size
[0156] The measured values of the diameters of at least 400 particles are used to perform calculation of (standard deviation / average particle diameter)×100 to determine the CV value of the particle diameter based on the number of particles.
[0157] (3) Volume average particle size
[0158] In the present disclosure, the volume median diameter is used as the volume average particle diameter.
[0159] The volume median diameter (Dv) of polymer particles 50 ) was measured using Nanotrac Wave II manufactured by Microtrac Bel Co., Ltd. and the analysis software Microtrac Date Management System manufactured by Microtrac Bel Co., Ltd.
[0160] Specifically, 0.02 g of the emulsion was mixed with 20 ml of sodium dodecylbenzenesulfonate diluent (concentration 0.02%) to prepare a sample dispersion, which was placed in a sample cuvette and measured under the conditions of solvent refractive index: 1.333, measurement time: 180 seconds, and number of measurements: 1 time.
[0161] Other setting conditions are: particle refractive index: 1.59, transmittance: transparent, shape: spherical, density: 1.00.
[0162] (4) Acid value
[0163] The acid value is the number of mg of potassium hydroxide required to neutralize the acid contained in 1 g of the resin. The acid value was determined by a method in accordance with JIS K0070 except that the solvent was THF.
[0164] (5) Solid content concentration
[0165] The solid content concentration of the emulsion was determined by heating 10 g of the emulsion at 190° C. for 60 minutes to evaporate water using a heat-drying moisture meter MX-50 manufactured by A&D Corporation.
[0166] (6) Yield
[0167] The yield was calculated as follows.
[0168] After the polymerization reaction, the emulsion was filtered through a double-layer nonwoven gauze (TREAT) (Fthree), and the total weight (A) g was measured.
[0169] Then, the solid content concentration (B) % was measured by the method described in (5).
[0170] The solid content weight after the polymerization reaction was calculated from the weight of the obtained emulsion after the polymerization reaction and the solid content concentration, and the result was divided by the theoretical solid content weight (C) g.
[0171] That is, it is calculated by yield = (A x B / 100) / C [%].
[0172] (7) Structural color rendering
[0173] The color development of the structure according to the Bragg's formula was visually confirmed.
[0174] (7-1) Wavelength and color assumed based on Bragg's formula
[0175] Bragg's formula gives the following equation.
[0176] λ max =(8 / 3) 1 / 2 ·D·(n ave 2 -sin 2 θ) 1 / 2
[0177] in,
[0178] D: diameter of colloidal particles
[0179] nave =n1φ1+n2φ2
[0180] n: refractive index
[0181] φ: volume fraction
[0182] Subscript 1: colloidal particles
[0183] Subscript 2: Air.
[0184] Specifically,
[0185] n1=1.592φ1=0.74 was used
[0186] n2=1.0φ2=0.26.
[0187] As the diameter of the colloidal particles, the number average particle diameter of the polymer fine particles was used.
[0188] The color development is determined by comparing the wavelength obtained by Bragg's equation with the wavelength of visible light.
[0189] (7-2) Whether there is structural coloration
[0190] It was visually confirmed whether the color expected according to Bragg's formula was developed.
[0191] [Raw materials, etc.]
[0192] Styrene (manufactured by Denka Co., Ltd.)
[0193] Acrylic acid (Mitsubishi Chemical Corporation)
[0194] Sodium styrene sulfonate (Toso Fine Chem Ltd.)
[0195] Sodium bicarbonate (manufactured by Fujifilm Wako Co., Ltd.)
[0196] Ammonium persulfate (manufactured by Kanto Chemical Co., Ltd.)
[0197] Carbon black (Mitsubishi Chemical Corporation)
[0198] [Example 1]
[0199] 98.4 parts of styrene and 1.5 parts of acrylic acid were mixed to prepare a monomer mixed liquid.
[0200] On the other hand, an auxiliary agent solution [A] was prepared by dissolving 0.1 parts of sodium styrene sulfonate and 0.15 parts of sodium hydrogen carbonate in 16.4 parts of ion-exchanged water.
[0201] 177.5 parts of ion exchange water was added to a reaction vessel equipped with a stirring device, a heating and cooling device, a nitrogen introduction device, and a raw material and auxiliary agent adding device. Then, the auxiliary agent solution [A] was added while rotating at 150 rpm to raise the internal temperature to 80°C.
[0202] Next, an initiator solution prepared by dissolving 0.42 parts of ammonium persulfate in 33.7 parts of ion-exchanged water was placed in the reaction container, and after 5 minutes, the monomer mixed solution was sequentially added dropwise over 3 hours.
[0203] After the dropwise addition of the monomer mixed solution was completed, polymerization treatment was carried out for 5 hours. During the polymerization reaction after the dropwise addition of the monomer mixed solution, ion exchange water was appropriately added so as not to change the liquid level.
[0204] Then, the polymerization reaction product was filtered through non-woven gauze (TREAT) to obtain an emulsion of polymer microparticles.
[0205] The obtained polymer microparticles had a number average particle size of 238 nm, a CV value of 3.8%, an acid value of 14.1 mgKOH / g, a solid content concentration of 29.1%, and a yield of 95%.
[0206] In addition, since only one type of monomer mixed solution was used, the polymer fine particles had a uniform resin composition, and Tg was 100° C. calculated according to Fox's equation.
[0207] The emulsion was diluted with ion exchange water to a solid content concentration of 10%, and a carbon black dispersion having a concentration of 20% was added to prepare a mixed sample so that the carbon black was 0.5 parts relative to 100 parts of the solid content of the emulsion. After the mixed sample was fully dispersed, it was applied to a smooth substrate using a dropper and dried at 55° C. together with the substrate to obtain a structure.
[0208] [Example 2]
[0209] 98.43 parts of styrene and 1.5 parts of acrylic acid were mixed to prepare a monomer mixed liquid.
[0210] On the other hand, an auxiliary agent solution [B] was prepared by dissolving 0.07 parts of sodium styrene sulfonate and 0.15 parts of sodium hydrogen carbonate in 16.4 parts of ion-exchanged water.
[0211] 177.5 parts of ion exchange water was added to a reaction vessel equipped with a stirring device, a heating and cooling device, a nitrogen introduction device, and a raw material and auxiliary agent adding device. Then, the auxiliary agent solution [B] was added while rotating at 150 rpm to raise the internal temperature to 80°C.
[0212] Thereafter, the same procedure as in Example 1 was carried out to obtain an emulsion of polymer fine particles.
[0213] As in Example 1, during the polymerization reaction after the completion of the dropwise addition of the monomer mixed solution, ion exchange water was appropriately added so as not to change the liquid level, but the added amount was slightly large, so the solid content concentration was a slightly low value.
[0214] The obtained polymer fine particles had an acid value of 13.0 mgKOH / g, a solid content concentration of 27.7%, and a yield of 95%.
[0215] In Example 2, the number average particle diameter was not measured, but was converted by number average particle diameter=volume average particle diameter×0.9775 to calculate a value of 308 nm.
[0216] In Example 2, the CV value of the particle size was not measured, but was converted by multiplying the CV value obtained by measuring the volume average particle size by 0.1131 to calculate 2.7%.
[0217] In addition, since only one type of monomer mixed solution was used, the polymer fine particles had a uniform resin composition, and Tg was 100° C. calculated according to Fox's equation.
[0218] Using the obtained emulsion, the same operation as in Example 1 was carried out to obtain a structure.
[0219] [Comparative Example 1]
[0220] Styrene 99.9 parts was prepared as a monomer.
[0221] On the other hand, an auxiliary agent solution [C] was prepared by dissolving 0.1 parts of sodium styrene sulfonate and 0.16 parts of sodium hydrogen carbonate in 16.6 parts of ion-exchanged water.
[0222] 181.6 parts of ion exchange water was added to a reaction vessel equipped with a stirring device, a heating and cooling device, a nitrogen introduction device, and a raw material and auxiliary agent adding device. Then, the auxiliary agent solution [C] was added while rotating at 150 rpm to raise the internal temperature to 80°C.
[0223] Next, an initiator solution prepared by dissolving 0.42 parts of ammonium persulfate in 34.2 parts of ion-exchanged water was placed in the reaction container, and after 5 minutes, the monomers were sequentially added dropwise over 3 hours.
[0224] After the dropwise addition of the monomers was completed, polymerization treatment was carried out for 5 hours. During the polymerization reaction after the dropwise addition of the monomers, ion exchange water was appropriately added so as not to change the height of the liquid level.
[0225] Then, the polymerization reaction product was filtered through non-woven gauze to obtain an emulsion of polymer particles.
[0226] The obtained polymer microparticles had a number average particle size of 273 nm, a CV value of 1.8%, an acid value of 3.2 mgKOH / g, a solid content concentration of 30.4%, and a yield of 86%.
[0227] In addition, since only one type of monomer was used, the polymer fine particles had a uniform resin composition, and Tg was 100° C. calculated according to Fox's equation.
[0228] Using the obtained emulsion, the same operation as in Example 1 was carried out to obtain a structure.
[0229] [Table 1]
[0230] Table 1
[0231]
[0232] As shown in Table 1, the wavelength at an angle of 0 degrees calculated according to the Bragg formula of Example 1 is 559 nm, and it is yellow-green when viewed visually, so it can be confirmed that the structural coloring is as expected. In addition, the wavelength at an angle of 45 degrees is 451 nm, and it is blue when viewed visually, so it can be confirmed that the structural coloring is as expected.
[0233] In Example 2, the color developed by visual observation at an angle of 0 degrees was red, and the color developed by visual observation at an angle of 45 degrees was green.
[0234] The wavelength of Comparative Example 1 at an angle of 0 degrees was 641 nm, which was visually red, and thus the expected structural coloration was confirmed. In addition, the wavelength at an angle of 45 degrees was 516 nm, which was visually green, and thus the expected structural coloration was confirmed.
[0235] From this, it was confirmed that Examples 1 and 2 had structural coloration similarly to Comparative Example 1 in which acrylic acid was not used as an acidic monomer.
[0236] In addition, it was confirmed that the structural color rendering property had no influence on the region with a small particle size (Example 1) or the region with a large particle size (Example 2) compared with Comparative Example 1. Therefore, it was confirmed that the structural color rendering property did not depend on the particle size.
[0237] Even when the polymer fine particles of Example 1 were polymerized at a high solid content concentration of about 29%, there were few debris during polymerization and adhesion to the inner wall of the polymerization apparatus, and the yield was as high as 95%.
[0238] Even when the polymer particles of Example 2 were polymerized at a high solid content concentration of about 28%, there were few debris during polymerization and adhesion to the inner wall of the polymerization apparatus, and the yield was as high as 95%.
[0239] In Comparative Example 1, the polymer fine particles generated a large amount of debris during polymerization and adhered to the inner wall of the polymerization apparatus, so the yield was reduced to 86%, which was inferior to Examples 1 and 2.
[0240] Furthermore, it was confirmed that the yield of the examples using acrylic acid as the acidic monomer was good in both the small particle size region (Example 1) and the large particle size region (Example 2) compared to Comparative Example 1. Thus, it was confirmed that the yield was not dependent on the particle size.
Claims
1. A polymer particle, wherein: The number average particle size is 50 to 450 nm, and the CV value of the particle size based on the number is 5% or less. The acid value is 5-38 mgKOH / g, The polymer particles are composed of polystyrene polymers. The content of styrene units in the polystyrene polymer is 90.0% by mass or more.
2. The polymer microparticle according to claim 1, wherein The polymer microparticles are particles having a uniform resin composition.
3. The polymer microparticle according to claim 1 or 2, wherein The Tg of the polymer particles is 50° C. or higher.
4. The polymer microparticle according to claim 3, wherein The Tg of the polymer fine particles is 60° C. or higher.
5. The polymer microparticle according to claim 1, wherein The polystyrene-based polymer contains acrylic acid units and / or methacrylic acid units.
6. An emulsion, wherein The polymer fine particles according to any one of claims 1 to 5 are dispersed in a medium mainly composed of water.
7. A structure, wherein: The polymer fine particles according to any one of claims 1 to 5 are arranged and colored.
8. An article, wherein The structure according to claim 7 is formed on a substrate.
9. The article according to claim 8, which is in the shape of a film.
10. A polymer particle having structural color development when arranged. The acid value is 5-38 mgKOH / g, The polymer particles are composed of polystyrene polymers. The content of styrene units in the polystyrene polymer is 90.0% by mass or more.
11. The polymer microparticle according to claim 10, wherein The polymer microparticles are particles having a uniform resin composition.
12. The polymer microparticle according to claim 10 or 11, wherein The Tg of the polymer particles is 50° C. or higher.
13. The polymer microparticle according to claim 12, wherein The Tg of the polymer fine particles is 60° C. or higher.
14. The polymer microparticles according to claim 10, wherein The polystyrene-based polymer contains acrylic acid units and / or methacrylic acid units.
15. An emulsion, wherein The polymer fine particles according to any one of claims 10 to 14 are dispersed in a medium mainly composed of water.
16. A structure, wherein: The polymer fine particles according to any one of claims 10 to 14 are arranged and colored.
17. An article, wherein The structure according to claim 16 is formed on a substrate.
18. The article according to claim 17, which is in the shape of a film.
Citation Information
Patent Citations
Vinyl polymer powder, curable resin composition, and cured product
WO2013062123A1
Ink composition for ink jet recording
CN101880494A
Structural color coating film-forming coating composition and method for forming multilayer coating film
JP2009249527A
Chromatic color fine particle capsule
JP2017160371A